Upaya Penanganan Pasien Laki-Laki Usia 60 Tahun dengan Diabetes Mellitus Tipe 2 Melalui Pendekatan Kedokteran Keluarga di Puskesmas Dewantara Kabupaten Aceh Utara - Siregar, Anisah Nazrah; Noviana Zara (Lembaga Pengembangan Kinerja Dosen, 2025)
A 60-year-old male patient presented with the chief complaint of numbness in both legs, which had been experienced for the past two years and had worsened over the last three months. This complaint was accompanied by persistent fatigue, even without engaging in strenuous physical activity. In addition, the patient reported frequent urination, especially at night (nocturia), and excessive thirst that had occurred for the past five years. The patient denied symptoms such as fever or disturbances in bowel movements. Regarding his medical history, the patient regularly consumed Glimepiride as part of his treatment for diabetes mellitus. Primary data were obtained through auto-anamnesis and physical examination during a home visit. During the visit, the family physician also completed the family folder and patient records to comprehensively document the patient’s health condition. Case assessment was carried out based on an initial holistic diagnosis, followed by continuous monitoring and final evaluation using both quantitative and qualitative approaches. The interventions provided included health education for the patient and his family regarding the causes and pathophysiology of diabetes mellitus. The physician also emphasized lifestyle modifications, such as adopting a balanced diet, engaging in light but regular physical activity, and maintaining adherence to prescribed medication. Furthermore, the patient was educated on the long-term management of diabetes mellitus and the importance of regular medical check-ups. The family physician also explained the potential complications that could arise, such as neuropathy, nephropathy, and retinopathy, so that the patient would be more compliant with treatment and preventive efforts. This comprehensive approach was expected to improve the patient’s quality of life while preventing further disease progression.